Oral Health and its Etiological Role in Behcet's Disease - (:unkn) unknown (DERI ZUHREVI HASTALIKLAR DERNEGI, 2009)
The etiological role of microbial factors has been hypothesized by Dr. Hulusi Behcet while he first described the entitiy. Although mechanisms of disease have not been clarified so far, significant data regarding the importance of microbial factors has been obtained. This data is concentrated mainly on oral health, oral flora elements and Streptococci. Accordingly, the role of oral health and microbial factors in the aetiology of the disease will be discussed in the first part of this review. Then, oral health care related topics will be highlighted for clinicians who treat and follow patients with Behcet's disease. (Turkderm 2009; 43 Suppl 2: 39-41)
Keywords: Oral health; Behcet disease; oral ulcer; oral hygiene; oral flora; PERIODONTAL FINDINGS; STREPTOCOCCUS-SANGUIS; TURKISH PATIENTS; MICROORGANISMS; EXPRESSION; ANTIGEN